The Influence of Ti Contents on the Properties of nc-TiC/a-C Nanocomposite Coatings - Lê Văn An; Bùi Xuân Lâm (Journal of Technical Education Science, 2006)
This paper concerns on the infl uence of Ti contents on the properties of nc-TiC/a-C nanocomposite coatings deposited via co-sputtering of Ti and graphite targets. Advanced characterization techniques such as XRD, XPS, TEM, nanoindenter, etc. were employed to determine the structures and properties of the coatings. Experimental results indicated that at low Ti compositions of less than 8 at.%, Ti exists in the coatings as an amorphous phase. From 8 to 45 at.%Ti, the formations of nanocomposite were confi rmed. Higher than that, the coatings were almost crystalline TiC. Nanocomposite may have a hardness comparable to that of DLC (about 33 GPa) but the residual stress is much lower. Such new nanocomposite show great potentials for engineering applications.